2019
DOI: 10.3390/cancers11030419
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FER Kinase Inhibits Melanoma Growth and Metastasis

Abstract: Melanoma is one of the most aggressive types of tumors and exhibits high metastatic potential. Fes-related (FER) kinase is a non-receptor tyrosine kinase that has been implicated in growth and metastasis of various epithelial tumors. In this study, we have examined the role that FER kinase plays in melanoma at the molecular level. FER-depleted melanoma cells exhibit impaired Wnt/β-catenin pathway activity, as well as multiple proteomic changes, which include decreased abundance of L1-cell adhesion molecule (L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…FER regulates cell-cell adhesion, promotes cell migration, and mediates signaling from the cell surface to the cytoskeleton via growth factor receptors [26]. A recent study also showed that targeting FER kinase can inhibit melanoma growth and metastasis [27].…”
Section: Discussionmentioning
confidence: 99%
“…FER regulates cell-cell adhesion, promotes cell migration, and mediates signaling from the cell surface to the cytoskeleton via growth factor receptors [26]. A recent study also showed that targeting FER kinase can inhibit melanoma growth and metastasis [27].…”
Section: Discussionmentioning
confidence: 99%
“…FER is ubiquitously expressed, and it is structurally characterized by an F-BAR domain, an SH2 domain, and a COOH-terminal tyrosine kinase domain ( 4 , 5 ). FER is overexpressed in various cancers, including pancreatic ductal adenocarcinomas ( 6 ), bladder urothelial cell carcinoma ( 7 ), melanoma ( 8 ), renal cell carcinoma ( 3 ), and breast cancer ( 9 ), and has been shown to enhance tumor cell metastasis and proliferation. However, the exact function of FER in HCC progression and the relevant biological molecular mechanism require further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to motility, FER expression has also been associated with proliferation of tumor cells (8,(20)(21)(22)(23). However, due to the limited number of known substrates, the molecular basis for its pro-proliferation activity remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%